Validation of protein precipitation and solid phase extraction clean-up procedure for simultaneous determination of trimethoprim and sulfamethoxazole in human plasma by HPLC-DAD - Bui, Van Hoi; Vu, Cam Tu; Phung, Ngoc Phuong Linh; Nguyen, Thi Thu; Duong, Thi Quynh Mai; Chu, Dinh Binh (JST: Engineering And Technology For Sustainable Development, 2025)
The combination of sulfamethoxazole (SMX) and trimethoprim (TMP) with a ratio of 5:1 is widely used in treating outpatient diseases against various gram-positive and negative bacteria as well as mycobacteria, parasites, and fungi. Monitoring these compounds in plasma is challenging due to the coexistence of complicated matrices. This study aimed to develop and validate the HPLC-DAD method combined with liquid-liquid extraction followed by an additional clean-up for the simultaneous determination of TMP and SMX in human plasma. The plasma sample was precipitated using the crashing solvent 1% acid formic in acetonitrile and then impurities were removed by a C18 sorbent (m = 100 mg). Two analytes were separated on a Hypersil Gold C8 column (100 mm × 2.1 mm i.d.; 3 µm particle size) under isocratic elution with 0.3% formic acid in water and methanol (80/20, v/v). A washing column with 100% MeOH was employed for 5 minutes after each injection to eliminate any potential impurities retained in the analytical column. The flow rate and the column temperature were constantly set up at 0.4 mL·min⁻¹ and 40 °C respectively. The maximum absorbance wavelengths were set 241 nm for TMP and 279 nm for SMX to achieve the highest selectivity and sensitivity. The method shows high recovery at 80.4% and 82.6% for TMP and SMX, respectively. The limit of quantification (LOQ) in plasma was 11.8 µg/L for TMP and 28.0 µg/L for SMX and intra- and inter-day precisions were less than 15% for both analytes. This validated method could be applied to pharmacokinetic studies in treatments.